Pengaruh Penambahan Follicle Stimulatins Hormone (FSH) dan Pregnant Mare's Serum Gonadrotropin (PMSG) dalam Sel Granulosa Terhadap Konsentrasi Progesteron pada Tingkat Maturasi Oosit - D. Dianti; Z. Udin; Jaswandi Jaswandi (Jurnal Peternakan Indonesia (Indonesian Journal of Animal Science), 2011)
This research was conducted to determine the effect of adding hormone FSH and PMSG in vitro oocyte maturation medium on maturation rate and hormone progeiterone. In this experiment,  oocyte derived from ovaries of slaughtered cattle at the slaughterhouse. Maturation medium using TCM-199 supplemented serum 10%, gentamicin 50ug/ml, FSH I0g/mlor PMSG 10 g/ml and the culture of granulosa cells lxl05 cells/ml. In each treatment unit is used 20 oocyt quality A and B in 100 mL of maturation medium. Randomized Blok Design in factorial (2x2x4) was used in this experiment. The Factor A culture (without cells and granulosa cell), B factor hormones (PMSG andFSH). Variables measured were the number maturation and progesterone hormone level in maturation medium by using RIA techniques. The results shown, there is no interaction of hormone addition in granulosa cell numbers on maturation level and progesterone concentration in maturation medium. Granulosa cell in maturation medium significantly (P<0.05) increased the number of oocyte maturation in vitro. The highest maturation was obtained from media with granulosa cells and FSH of 71.25%, while the highest progesterone obtained from media with granulosa cells and PMSG 1.40 ng / ml.